2005
DOI: 10.1148/radiol.2341030931
|View full text |Cite
|
Sign up to set email alerts
|

Cryotherapy for Breast Fibroadenomas

Abstract: Cryotherapy of fibroadenomas is a safe, effective, and virtually painless clinic-based (ie, outpatient) treatment option with good cosmesis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
79
1

Year Published

2005
2005
2023
2023

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 120 publications
(82 citation statements)
references
References 23 publications
2
79
1
Order By: Relevance
“…Littrup et al (9) reported that 42 biopsy-confirmed fibroadenomas in 29 patients who underwent percutaneous cryoablation. All patients were very comfortable with the resolution of palpable mass effect and cosmetic results.…”
Section: Clinical Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Littrup et al (9) reported that 42 biopsy-confirmed fibroadenomas in 29 patients who underwent percutaneous cryoablation. All patients were very comfortable with the resolution of palpable mass effect and cosmetic results.…”
Section: Clinical Resultsmentioning
confidence: 99%
“…Compared with the above techniques, ultrasound-guided cryoablation of fibroadenomas has been shown to be a costeffective alternative with a low morbidity risk (7)(8)(9)15,19). A number of potential advantages include: v Cryoablation for tumor destruction is well suited for ultrasound guidance and monitoring because the hyperechoic effect obtained with ice-ball formation can be easily identified and therapy can be directed with precision; v This technique is a mini-invasive and virtually painless procedure, can be performed under local anesthesia in an office-based breast clinic; v There is an excellent cosmesis without tissue removal and minimal scarring.…”
Section: Discussionmentioning
confidence: 99%
“…9 Others have shown that cryoablation is highly successful in treating fibroadenomas and other benign breast lesions. [10][11][12][13][14][15] In 2001, the Visica™ system for cryoablation of fibroadenomas was approved by the US Food and Drug Administration (FDA). 16,17 Cryoassisted lumpectomy is another application of this technique for the localization and removal of non-palpable breast lesions.…”
Section: R Y O a B L A T I O N To D A Ymentioning
confidence: 99%
“…22 An injection of saline may be used to increase the distance between the tumor and skin where the two are too close, avoiding hypothermiainduced skin damage. 15 The treated area is left in place to be absorbed by the host inflammatory response.…”
Section: R Y O a B L A T I V E Te C H N I Q U Ementioning
confidence: 99%
See 1 more Smart Citation